El último mohicano - Cooper, James Fenimore, 1789-1851 (Colección Biblioteca Nueva de aventuras ;, 2013)
In 1757, the third year of the French and Indian War, Hawkeye, a colonial scout, and his friends, Chingachkook, a chief of the Mohicans, and his son Uncas risk their lives to guide two English sisters through hostile territory and evade the evil Huron, Magua, who is determined to destroy them.